Learning Innovation Management on Effective Classes at SMPIT Cordova Samarinda - Hanim, Zaenab; Masyni, Masyni; Soe`oed, Rahmad; Asiah, Siti Nor (Dinamika Ilmu, 2019)
The research is intended to find out (1) the concept of learning innovation, (2) the implementation of learning innovation management functions, (3) the implication of learning innovation management, and (4) obstacles and solutions of the implementation of learning innovation management at effective classes at Integrated Islamic Secondary School (SMPIT) Cordova Samarinda. This research used a qualitative approach with case study and the data was collected through deep interview, observation and documentation. The informans of the research are the head and his vice of the foundation, coordinator of the effective classes, teachers and students. The data was analysed by using descriptive technique. For the research findings, it was  found that (1) the concept of learning innovation for effective classes is built through middle input with an effective learning process and produces an effective output; (2) the implementation of learning innovation management functions of effective classes was carried out through planning design by determining input sellection standard, an effective process standard, an effective output standard, learning innovation organization through enriched curriculum, time allocation, teachers’ roles and duties, learning  sources,  learning innovation  through moving class, a standardized teachers, IT-based management, full day school program, and  three evaluations of learning innovation, namely test and non-test with mastery learning standard, and high competition class assessment; (3) the implication of learning innovation management covers integrated learning management system, better teacher qualification standard, and increase school reputation; and (4) obstacles and solution disrupt the implementation of learning innovation management of effective classes at SMPIT Cordova Samarinda.